(untitled) (La U Investiga, 2020)
The legal political context of the Country and the World Health Organization recognize that all people have the same right not to be subjected to violence, persecution, discrimination and / or stigmatization. The objective is to identify the factors that affect health care for lesbians, geys, bisexuals, transgenders and intersex and the evaluation of knowledge about the care regulations by Health professionals at Hospital San Vicente de Paúl Ibarra Ecuador. Descriptive, analytical and crosssectional methodology is used, with a mixed approach. The study group is made up of 179 health professionals, and 40 LGBTI people, As a data collection technique, two instruments are applied, the first aimed at health professionals, which consisted of 15 items, and the second instrument, structured in 20 items with open and closed questions, aimed at LGBTI people where the health care needs of this group, the data were processed in Microsoft Excel. Results: Three-quarters of the age group belong to the ages between 24 and 33 years, single, and self-identify as homosexuals. In health personnel, 62% belong to the female gender between 29 and 34 years old, and they present a marked lack of knowledge regarding the regulations for the care of these human beings. It is essential that health professionals assume the commitment to improve health care and apply the regulations, promoting healthy environments without discriminatory attitudes. LGBTI people consider that awareness campaigns should be promoted and educational talks on health care as a right should be developed.